In situ crystallization and crystal structure determination of chlorobenzene - Nath, Naba K.; Naumov, Panče (Society of Chemists and Technologists of Macedonia, 2015)
The crystal structure of chlorobenzene, which is liquid at ambient conditions of pressure and temperature, was determined after in situ crystallization by using Optical Heating and Crystallization Device (OHCD) coupled to a single crystal X-ray diffractometer. Chlorobenzene crystallizes in the orthorhombic space group Pbcn with one symmetry-independent molecule in the asymmetric unit. In the crystal structure, type II Cl Cl interactions form zigzag chains that are assisted by C—H π interactions. Hirshfeld surface analysis revealed five types of intermolecular contacts.